Mechanisms For Improving Piano Performance In Training Activities Based On A Systematic Approach (Czech Journal of Multidisciplinary Innovations, 2025)
The activities of specialized schools of art and culture play an important role in ensuring the effectiveness of the system of continuous music education. In particular, classes organized on the basis of a systematic approach in the pedagogy of piano performance expand the opportunities for students to raise their performance, technical and artistic expressive skills and abilities to a new qualitative level. The article presents analytical considerations on the results of research conducted on this topic.